Pengembangan Kromatografi Cair Kinerja Tinggi yang Sederhana untuk Analisis Kurkumin dalam Plasma Manusia In-Vitro - Novi Yantih; Endah Giyah Wahyuningsih; Deni Rahmat; Yunahara Farida (JURNAL ILMU KEFARMASIAN INDONESIA, 2020)
Curcumin has antioxidant, antiinfl ammatory, antitumor, apoptotic-inducing, andantiangiogenesis eff ects. In order to study the pharmacokinetics of curcumin, a method for analysisof curcumin in plasma levels is required. The aim of this study was developing of a simple HighPerformance Liquid Chromatography (HPLC) for analysis curcumin in human plasma in-vitro. TheHPLC system was using isocratic technique in column reversed phase of C18 (Reliant® RP-18ecolumn (4.6x250 mm; 5 μm)) and mobile phase of acetonitrile–acetic acid–aquabidest (60:1:39) at fl owrate of 1.0 mL/min. Irbesartan was used as an internal standard. Detector was performed at a wavelengthof 428 nm for curcumin and 270 nm for irbesartan. Linearity test shown linear results with a correlationcoeffi cient (r) of 0.9970. LLOQ value was 0.0196 μg/mL with a diff erentiation value of 10.48-18.09%.The accuracy and precision of this method met requirement with a diff erentiation value and relativestandard deviation of between -5.51-3.04 % and 1.04-1.86 %, respectively. Recovery of this method was94.74-103.12%. This method provides good selectivity for the analysis curcurmin in human plasma.The developed of HPLC was a simple and valid method for analysis curcumin in human plasma.